2020
DOI: 10.1111/1759-7714.13295
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia induced changes in miRNAs and their target mRNAs in extracellular vesicles of esophageal squamous cancer cells

Abstract: Background Extracellular vesicles (EVs) are endogenous membrane vesicles with a diameter of 30–200 nm. It has been reported that hypoxic cancer cells can release numerous EVs to mediate multiple regional and systemic effects in the tumor microenvironment. Methods In this study, we used ultracentrifugation to extract EVs secreted by TE‐13, an esophageal squamous carcinoma (ESCC) cell line during normoxia and hypoxia and performed high‐throughput sequencing to detect exosomal miRNAs. Gene ontology (GO) and KEGG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 41 publications
0
31
0
Order By: Relevance
“…To identify novel 5p- and 3p-derived miRNAs and known miRNAs, unique sequences with lengths of ~18–26 nucleotides were mapped to specific species precursors in miRBase 22.0 by BLAST search as previously described ( 37 , 38 ). Briefly, the unique sequence mapping to specific species' mature miRNAs in hairpin arms identified known miRNAs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify novel 5p- and 3p-derived miRNAs and known miRNAs, unique sequences with lengths of ~18–26 nucleotides were mapped to specific species precursors in miRBase 22.0 by BLAST search as previously described ( 37 , 38 ). Briefly, the unique sequence mapping to specific species' mature miRNAs in hairpin arms identified known miRNAs.…”
Section: Methodsmentioning
confidence: 99%
“…Then the unique sequence mapping to the other arm of known specific species precursor hairpin opposite to the annotated mature miRNA-containing arm considered be novel 5p- or 3p-derived miRNA candidates. Furthermore, the remaining sequences were mapped to other selected species' precursors (with the exclusion of specific species) in miRBase 22.0 by BLAST search against the specific genomes, and the sequences containing hairpin RNA structures were predicted from the flank 80-nt sequences using RNAfold software ( http://rna.tbi.univie.ac.at/cgi-bin/RNAfold.cgi ) in order to predict novel candidate miRNAs more accurately ( 37 , 38 ).…”
Section: Methodsmentioning
confidence: 99%
“…Because miRNAs are important intercellular signalling molecules encapsulated by EVs, we inferred that they may be associated with H-EV-induced radioresistance in OSCC. We previously reported highthroughput miRNA-seq results in EVs derived from both normoxic and hypoxic conditions of OSCC cells, nding that miR-340-5p is highly expressed in H-EVs derived from OSCC cells (15). Previous studies have reported that miR-340-5p plays a dual role in cancer development and progression.…”
Section: Mir-340-5p Is Highly Expressed In H-evs and Promotes Radiorementioning
confidence: 99%
“…Fifty miRNA was up-regulated and 34 miRNA was down-regulated significantly in hypoxictreated cell lines, and these differentially expressed miRNAs are mainly involved in cancer-related and phospholipase D signaling pathways. 64 Base on the studies of kidney cancer and breast cancer cells, it was speculated that the enhanced phospholipase D activity was necessary for stable expression of HIF-1 and HIF-2 and aerobic glycolysis of cells. [65][66][67] Exosomes are special types of EVs with a diameter of 50-200nm.…”
Section: Hypoxia Acidosis and Nutrient Depletion Are The Basic Charmentioning
confidence: 99%